PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP HASIL BELAJAR MATEMATIKA KELAS XI MAN 2 BUKITTINGGI - Afifah, Suha (Departemen Matematika, 2025)
Learning outcomes in mathematics are a measure of how well students have mastered the subject and how much progress they have made in achieving their goals. However, class XI MAN 2 Bukittinggi still has low scores, as evidenced by daily assessment and observation data. The purpose of the study was to test and characterize the effectiveness of the Think Talk Write (TTW) model in mathematics education, compared to more traditional approaches. The study used a quasi-experimental design with a control group that was only given a post-test and not an equivalent post-test. Class XI of MAN 2 Bukittinggi in the 2024-2025 academic year became the study population. Class XIF.5 served as the experimental group and class XIF.9 as the control group, which were selected using simple random sampling. The research tool used was descriptive exam questions. The null hypothesis (H0) was rejected because the t-test results indicated the P-value (0.000) was lower than the significance level (α = 0.05). This indicates that the TTW model produces superior learning outcomes compared to the traditional approach in class XI MAN 2 Bukittinggi.Keywords– Mathematics Learning Outcomes, TTW Cooperative Learning Model, Conventional Learning Model